Preliminary Results of an Earthquake Early Warning System in Costa Rica - Porras, Juan; Massin, Frédérick; Arroyo-Solórzano, Mario; Arroyo, Ivonne; Linkimer, Lepolt; Böse, Maren; Clinton, John (Frontiers in Earth Science, 2021)
We analyze the performance of a prototype Earthquake Early Warning system deployed at the National Seismological Network of Costa Rica in collaboration with the Swiss Seismological Service by presenting the real-time performance during six earthquakes (Mw 5.1-6.4) that took place during 2018 and 2019. We observe that, despite only limited efforts to optimize the existing network of 158 stations, for Earthquake Early Warning purposes, the network density allows fast determination of source parameters using both the Virtual Seismologist and the Finite Fault Rupture Detector algorithms. Shallow earthquakes on or near-shore are routinely identified within 11-20 s of their occurrence. The warning times for the capital city of San Jose are of 43 s for epicenters located at 220 km, like for the Mw 6.4 Armuelles earthquake. On the other hand, during the time analyzed, the Earthquake Early Warning system did not provide positive warning times for earthquakes at distances less than 40 km from San Jose. Even though large (Mw > 7) distant historical earthquakes have not caused heavy damage in San Jose, there is potential for developing an Earthquake Early Warning system for Costa Rica, especially for the purposes of rapid earthquake notifications, disaster response management, and seismic risk mitigation.